2016
DOI: 10.1016/j.healun.2016.01.659
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acute Exacerbation of Idiopathic Pulmonary Fibrosis on Outcomes after Lung Transplantation

Abstract: greater likelihood of pulmonary hypertension. However in spite strong trend none of these achieved statistical significance. The low number of patients transplanted during exacerbation limited the statistical significance of this analysis. Continued evaluation of outcomes in this population will be needed to further define the role of lung transplantation during IPF exacerbation.( 631)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previous retrospective studies have no difference in posttransplant 1 y survival between IPF patients transplanted at steady state and patients transplanted during an AE. [25][26][27] Another published abstract demonstrated higher rates of PGD in patients transplanted during AE-IPF, albeit not significantly. 27 However, a major study from 2018 showed a significant difference in survival, both short term and longer term, between those patients transplanted with stable IPF and those with AE-IPF (Table 3).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous retrospective studies have no difference in posttransplant 1 y survival between IPF patients transplanted at steady state and patients transplanted during an AE. [25][26][27] Another published abstract demonstrated higher rates of PGD in patients transplanted during AE-IPF, albeit not significantly. 27 However, a major study from 2018 showed a significant difference in survival, both short term and longer term, between those patients transplanted with stable IPF and those with AE-IPF (Table 3).…”
Section: Discussionmentioning
confidence: 96%
“…[25][26][27] Another published abstract demonstrated higher rates of PGD in patients transplanted during AE-IPF, albeit not significantly. 27 However, a major study from 2018 showed a significant difference in survival, both short term and longer term, between those patients transplanted with stable IPF and those with AE-IPF (Table 3). 19 In contrast, our study, which is the largest cohort of IPF patients undergoing LTX studied thus far, demonstrated no difference in posttransplant mortality in the early postoperative period or at 3 y posttransplant between the 2 groups.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, in some institutions, patients may be emergently evaluated and urgently listed for lung transplantation candidacy during an otherwise lethal acute exacerbation. Very few limited studies have addressed the problem of outcomes after a lung transplant in stable condition as compared with an acute exacerbation condition [25,26,27] and concluded with a recommendation of still going on towards transplant even during the acute worsening of the clinical condition. However, these experiences are limited to single-center retrospective studies with short follow-up, until 1 year of observation after transplant and without long-term mortality analysis.…”
Section: A Focus On Acute Exacerbation: a Good Or A Bad Indication?mentioning
confidence: 99%